Technology Transfer, Development, Deployment and Productivity Performance in Pakistan - Irfan Ali; Zafar Mahmood (NUST Journal of Social Sciences and Humanities, 2021)
Productivity (TFP) performance is not only influenced by the direct effects of human capital, R&D (technology development)), embodied and disembodied forms of technology transfer and know-how through capital imports, FDI and use of foreign IPRs (technology transfer activities), but importantly is indirectly affected by compo-nents like the interactive effects of machinery and equipment imports, royalties and licenses fee payments, FDI, human capital and technology deployment. In this context, we analyzed internal technology building capabilities, trade-related technology transf-er activities and foreign technology absorption capabilities. The ARDL technique demonstrates that stable long-run association exists amongst all the chosen variables. The results indicate that investment in human capital boost the TFP, in addition expenditures on R&D, imports of machinery are crucial determinants of TFP growth. Surprisingly, FDI appears with a negative sign but the indirect effect of FDI through its interaction with human capital is positive. This indicates that FDI in the presence of human capital plays a favourable role in enhancing TFP. Moreover, the imports of machinery directly and indirectly, in association with both human capital and R&D, increase the growth of TFP. These findings provide evidence that internal technology building capabilities enhances the TFP growth significantly; while, embodied form of technology transfer has a positive and significant impact on the growth of TFP; whereas, disembodied technology transfer exerts positive but statistically insignificant impact on TFP growth. Furthermore, the study lends support for the existence of strong foreign technology absorption capabilities.